Finding common ground : consensus in research ethics across the social sciences - Iphofen, Ron (Emerald Group Publishing Limited : Emerald Publishing Limited, 2017)
This volume addresses concerns about the impact of current systems for the management of research ethics in the social sciences. Many procedures in place are seen as inappropriate as they were originally designed for use in biomedical research. The content identifies areas of 'common ground', core ethics principles and areas of particular concern.
Keywords: Social sciences and ethics.; elektronické knihy; electronic books